Social transformation in India - Dak, T.M. (ed.) (Delhi, Ajanta Publisher, 1990)
The volume, as a tribute to Professor Madan Lal Sharma, was planned by his one time colleagues and disciples to facilitate him on the occasion of his superannuation as Professor of Sociology and Dean, Postgraduate Studies, Haryana Agricultural University, Hisar, on attaining the age of sixty on 31.3.1990. The area of social change and economic development particularly in Indian Rural Society has always been dear to professor Sharma throughout this over three-decades of teaching career. It was, therefore, considered befitting to bring out a volume focusing on the theme he consistently nurtured under the title "Social Transformation in India". The volume contains nineteen papers contributed mainly by those social scientists who remained closely associated with him as a colleague or student and had an opportunity to work with him. The volume was planned only in the middle of December 1989. Despite the contributors have responded favourably to out request and contributed their papers at a very short notice. The publication of the book on the choosen theme is important by itself in view of the fact that the study and pratice of development and change were pre-occupied with documentation of technological reforms and economic transformation with little attention to the resultant structural alterations. The social science literature offers enough evidence to suggest the traditional institutional structure, inherited by India was evolved to meet the goals of stability security and survival of the society and therefore, could not function effectively as a vehicle for development and change. The planned development in India, since early-fifties set for itself the goals of institutional adaptation of redical nature and institutional innovation to serve the demands of development and change. How far this could be achieved is a matter of great interest to all those concerned walk social transformation in India. This volume addresses to this central question.
Keywords: Social change